An Empirical Study of The Cocoa, Rubber and Economic Growth in Malaysia - Taasim, Shairil Izwan; Yusoff, Remali (Journal of Techno-Social, 2019)
The Malaysian plantation industry is an integral part of the agricultural sector. Cocoa and rubber products’ trade is very important to the Malaysian economy and the global agricultural industry. The purpose of this study is to evaluate the relationship between cocoa, rubber and economic growth in Malaysia. To examine this linkage, we use time series from 1972 to 2016. Based upon the results we examined for both the short-run and long-run by employing Johansen co-integration and Vector Error Correction Model (VECM). These findings showed that the cocoa and rubber had an impact on the GDP for long run relationship.